INSTRUMENTAL PROVISION OF THE MARKETING COMPONENT OF THE ECONOMIC SECURITY OF AN ENTERPRISE IN THE CONDITIONS OF DIGITAL BUSINESS TRANSFORMATION - CHAIKOVSKA, Inna; ZAKRYZHEVSKA, Iryna; KARPENKO, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The work has formed a system of instrumental support for the marketing component of the economic security of an enterprise in the context of digital business transformation: a comprehensive combination of marketing tools provided by the concepts of 4P, 4C and Marketing 6.0 (MT 4P+MT 4C+MT 6.0). It is this combination of marketing tools that will ensure the optimal level of the marketing component of the economic security of an enterprise. The authors reflect the components of 4P and 4C marketing, and also present the evolution and specifics of the concepts of Marketing 1.0, 2.0, 3.0, 4.0, 5.0 and Marketing 6.0. The main tools of Marketing 6.0 are reflected, which allow you to recreate the work of marketing experts: artificial intelligence, NLP, IoT, robotics, augmented and virtual reality, blockchain. The components of Marketing 5.0 and the corresponding tools for their provision are also analyzed: Data-driven marketing (analytical tools, for example, Google Analytics); Predictive marketing (tools for analyzing big data (Big Data); BI-systems for data visualization; CRM-systems; data analysis platforms; tools for A/B testing; platforms for marketing automation); Contextual marketing (artificial intelligence technologies); Augmented Marketing (machine learning algorithms and artificial intelligence technologies); Agile Marketing (Agile tools).
Keywords: economic security of the enterprise; marketing component of economic security of the enterprise; marketing tools; digital economy; digital transformation of business; Marketing 6.0